2011
DOI: 10.1111/j.1365-2729.2011.00418.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of electronic outlining on students' argumentative writing performance

Abstract: This study examined the effect of electronic outlining on the quality of students' writing products and how outlining affects perceived mental effort during the writing task.Additionally, it was studied how students appropriate and appreciate an outline tool and whether they need explicit instruction in order to engage in planning. To answer these questions, the writing products and self-report data from 34 tenth-grade students of a Dutch pre-university school were analyzed. Students wrote two similar argument… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…Results from previous studies (De Smet, Brand-Gruwel, Broekkamp, & Kirschner, 2012;De Smet, Broekkamp, Brand-Gruwel, & Kirschner, 2011) suggest positive effects of electronic outlining on the quality of students' argumentative texts. The tool helped students better present their texts' structure and decreased perceived mental effort.…”
Section: Electronic Outliningmentioning
confidence: 77%
See 2 more Smart Citations
“…Results from previous studies (De Smet, Brand-Gruwel, Broekkamp, & Kirschner, 2012;De Smet, Broekkamp, Brand-Gruwel, & Kirschner, 2011) suggest positive effects of electronic outlining on the quality of students' argumentative texts. The tool helped students better present their texts' structure and decreased perceived mental effort.…”
Section: Electronic Outliningmentioning
confidence: 77%
“…Based on the theoretical notions and prior studies on (electronic) outlining described above (De Smet et al, 2011;2012;Kozma, 1991;Walvoord et al, 1995) it is expected (H1) that electronic outlining leads to better structured texts. Second, it is hypothesised (H2) that electronic outlining decreases perceived mental effort while writing (cf.…”
Section: Research Questions and Hypothesesmentioning
confidence: 95%
See 1 more Smart Citation
“…Regarding the reliability of this assessment protocol, de Smet et al (2011) reported an interrater reliability of q = .84 for Total Text Structure and q = .87 for Structure Presentation. Regarding the reliability of Hierarchical Elaboration of Arguments, 10 random argumentative texts were rated by two researchers.…”
Section: Mjr De Smet Et Al / Computers In Human Behavior XXX (201mentioning
confidence: 98%
“…Despite the fact that such a design has minimal internal validity and no external validity (Sytsma, 2002), we have chosen this design because of time restrictions of the project. A within-subjects design does not require a placement test that cancels out possible differences in competencies between participants (de Smet et al, 2011). A total number of minimal 60 students of university as well as college institutions will be tested.…”
Section: Effectiveness Analysis and Further User Studymentioning
confidence: 99%